2009
DOI: 10.1158/1055-9965.epi-08-0531
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Aerobic Exercise on Insulin and Insulin-like Growth Factors in Breast Cancer Survivors: The Yale Exercise and Survivorship Study

Abstract: Background: High insulin and insulin-like growth factor-I (IGF-I) levels may be associated with an increased breast cancer risk and/or death. Given the need to identify modifiable factors that decrease insulin, IGF-I, and breast cancer risk and death, we investigated the effects of a 6-month randomized controlled aerobic exercise intervention versus usual care on fasting insulin, IGF-I, and its binding protein (IGFBP-3) in postmenopausal breast cancer survivors. Methods: Seventy-five postmenopausal breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
206
0
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(239 citation statements)
references
References 39 publications
16
206
0
8
Order By: Relevance
“…We found that two months of exercise training decreased circulatory IGF-1, when compared with the control group. This is in line with the results of previous studies (7,16,17,26). Evidence indicates that reduction of serum IGF-1 by lifestyle modification reduces the number of cancer cells, slows tumor progression and increases apoptosis in tumor cells (3, 7).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that two months of exercise training decreased circulatory IGF-1, when compared with the control group. This is in line with the results of previous studies (7,16,17,26). Evidence indicates that reduction of serum IGF-1 by lifestyle modification reduces the number of cancer cells, slows tumor progression and increases apoptosis in tumor cells (3, 7).…”
Section: Discussionsupporting
confidence: 92%
“…However, the exact mechanism of this phenomenon is not clear. Several biological mechanisms could explain exercise training-induced decrease in IGF-1, including increased post-receptor insulin signalling, increased glucose transporter protein and mRNA, decreased release and increased clearance of free fatty acids, and increased muscle glucose delivery (17,27). In addition, decrease in pro-inflammatory cytokines (28) and increase in skeletal muscle IGF-1R density and activation may be other potential mechanisms for the exercise-induced reduction in systemic levels of IGF-1 (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors identified significant differences between the two groups (−10.9%). Irwin et al 7 reported a 3% decrease in IGF-I plasma levels in the exercise group and a 5.5% increase in the control group, representing a clinically significant difference (p = 0.089). The exercise program in that study comprised moderate-intensity aerobic exercise for 150 min per week for 24 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…6 Several studies have demonstrated a relationship between high concentrations of IGF-I and the risk of recurrence and death in BCSs. 7 There is now ample epidemiological and experimental evidence for the role played by physical activity in the rehabilitation of female BCSs. Meta-analyses and systematic reviews of randomized clinical trials have confirmed the positive effects of physical exercise on biological and cardiopulmonary function and the reduction of sex hormones, body fat mass, insulin, IGFs, adipocytokines, and mammographic density, as well as increased immune function and improved antioxidant defense systems and QOL in BCSs.…”
Section: Introductionmentioning
confidence: 99%